Sex differences in executive functioning and latent herpesvirus reactivation among bereaved and nonbereaved individuals. (11th July 2019) - Guevara, Jasmin E.; Gilbert, Sarah; Murdock, Kyle W.; Stowe, Raymond P.; Fagundes, Christopher P.
Abstract: The death of a spouse is a highly stressful event. Better executive functioning has been shown to benefit men to a greater degree than women during stress. We evaluated potential sex differences in stress and immune dysregulation among control and bereaved participants who completed a self‐report measure of perceived stress, neuropsychological measures of inhibition and updating/monitoring of information in working memory, and a blood draw to measure Epstein–Barr virus (EBV) antibody titres. Moderation analyses were conducted to test the hypothesis that better inhibition would be associated with less stress and immune dysregulation among male bereaved participants compared with female bereaved participants. Bereaved females demonstrated greater EBV antibody titres than bereaved males. Male bereaved participants benefited from better inhibition, as evidenced by fewer EBV antibody titres, whereas bereaved female participants did not. In the control group, males with high inhibition reported lower stress than males with low inhibition. Present study results are an important step towards identifying those at greatest risk of stress and poor health.